2019
DOI: 10.3390/toxins11070406
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Isoquinoline Alkaloids and Extracts from Chelidonium majus against Pathogenic Bacteria and Candida sp.

Abstract: Chelidonium majus (Papaveraceae) extracts exhibit antimicrobial activity due to the complex alkaloid composition. The aim of the research was to evaluate the antimicrobial potential of extracts from wild plants and in vitro cultures, as well as seven major individual alkaloids. Plant material derived from different natural habitats and in vitro cultures was used for the phytochemical analysis and antimicrobial tests. The composition of alkaloids was analyzed using chromatographic techniques (HPLC with DAD dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 26 publications
3
47
1
1
Order By: Relevance
“…Alkaloids are nitrogenous compounds characterized by their alkaline nature, which aids the inhibition of cell respiration, intercalates with DNA, and inhibits various enzymes involved in replication, transcription, and translation [147]. Plant-based bioactive compounds such as quercetin (1), nobiletin (51), myricetin (43), tangeritin (52,) genistein (31), apigenin (8), chrysin (24), kaempferol (23), and 3, 6, 7, 30, 40-pentahydroxyflavone (39) have been recognized as noteworthy DNA gyrase inhibitors, which are essential for DNA replication in prokaryotes including V. harveyi, B. subtilis, M. smegmatis, M. tuberculosis, and E. coli [146,[148][149][150][151].…”
Section: Inhibition Of Prokaryotic Dna Replicationmentioning
confidence: 99%
“…Alkaloids are nitrogenous compounds characterized by their alkaline nature, which aids the inhibition of cell respiration, intercalates with DNA, and inhibits various enzymes involved in replication, transcription, and translation [147]. Plant-based bioactive compounds such as quercetin (1), nobiletin (51), myricetin (43), tangeritin (52,) genistein (31), apigenin (8), chrysin (24), kaempferol (23), and 3, 6, 7, 30, 40-pentahydroxyflavone (39) have been recognized as noteworthy DNA gyrase inhibitors, which are essential for DNA replication in prokaryotes including V. harveyi, B. subtilis, M. smegmatis, M. tuberculosis, and E. coli [146,[148][149][150][151].…”
Section: Inhibition Of Prokaryotic Dna Replicationmentioning
confidence: 99%
“…The authors compared also the monomer/dimer structure-antibacterial activity relationship, which brought important information on the mechanism of activity against S. aureus. The research presented by Zielińska and her colleagues [10] included them in the same area of research. The authors showed a range of research on the presence of alkaloids in organs of Chelidonium majus and combined these observations with the activity of extracts and single metabolites against certain microorganisms: S. aureus, Pseudomonas aeruginosa, Klebsiella pneumonia, Escherichia coli, and Candida albicans.…”
mentioning
confidence: 99%
“…Based on our research, further detailed analyses would allow us to determine the proportions between individual compounds, especially these of alkaloid and polyphenol groups contained in many other Corydalis species, and thus select the most valuable raw material. This would be justified because of the wide spectrum of biological activities of both isoquinoline alkaloids and polyphenolic compounds confirmed in the literature, especially antimicrobial [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier studies, individually tested protopine and coptisine, presented antibacterial properties against S. aureus at a concentration of less than 50 mg/L (73% CFU reduction), while berberine was less effective (MIC at 125 mg/L). Additionally, coptisine showed antibacterial activity against P. aeruginosa and C. albicans , similar to allocryptopine (MIC at > 50–125 mg/L) [ 35 ]. Protopine and protoberberine derivatives such as coptisine and berberine have several pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%